Concentration of Vitamin C and Vitamin E Supplementation in Artemia Sp. on The Level of Stress Resistance, Survival, and Growth of Banggai Cardinalfish (Pterapogon Kauderni Koumans, 1933) - Sari, Devi Elvina (Raudhah Publisher, 2024)
The Banggai cardinalfish (Pterapogon kauderni) is an endemic marine ornamental fish from Indonesia, facing population decline due to habitat degradation and overexploitation. Controlled cultivation is essential for conservation; however, challenges such as stress, low survival rates, and slow growth remain significant. This study employs a qualitative research approach through literature review and library research to analyze the impact of vitamin C and E supplementation in Artemia sp. on stress resistance, survival, and growth performance of P. kauderni. Vitamin C and E are known antioxidants that mitigate oxidative stress and enhance immune responses in fish. Previous studies indicate that optimal supplementation levels can improve metabolic efficiency, stress tolerance, and overall survival rates in aquaculture species. Our findings suggest that a balanced combination of vitamin C (230 mg/L) and vitamin E (115 mg/L) in Artemia sp. provides the most effective results in reducing stress-induced glucose levels, increasing survival rates, and improving growth performance. These results highlight the potential of dietary antioxidant supplementation as a sustainable strategy for P. kauderni aquaculture and conservation. Further research is recommended to explore long-term effects and adaptability in different aquaculture settings.